Analisis Pengetahuan Technological Pedagogical Knowledge Guru Biologi pada Sekolah Penggerak di Makassar - Jaelani, Nurkhafifah; Arsal, Andi Faridah; Bahri, Arsad (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
The learning paradigm of the 21st century demands that educators have the ability to use technology, information, and communication. Teachers' understanding of digital technology in classrooms is becoming increasingly important in education. The quality of education is influenced by the competence of the teacher. Teachers who adapt to technological developments provide more relevant and effective learning. Technological Pedagogical Knowledge (TPK) is a set of understandings about how to implement change in learning using technology as its support. It happens through the interaction of pedagogical and technological approaches. This research is descriptive quantitative aimed at providing an overview of knowledge Technological Pedagogical Knowledge Teacher of Biology at the Sekolah Penggerak in Makassar. The sample used was 13 biology teachers at the Sekolah Penggerak in Makassar. Data is collected through self-assessment of the respondents. The results of the study showed that the average percentage of Technological Knowledge (TK) aspects of 88.5% in the category was very good. The average percentage of Pedagogical Knowledge (PK) aspects of 87.5% in the category was very good. The average percentage of Technological Pedagogical Knowledge (TPK) aspects of 83.3% in the category was very good. In general, the Knowledge of Technological Pedagogical Knowledge Teacher of Biology at the Sekolah Penggerak in Makassar is in the very good category with a percentage of 86.9%. One of the key factors of the high value of Technological Pedagogical Knowledge (TPK) Teacher of Biology at the Sekolah Penggerak in Makassar is the reinforcement effort carried out at all levels of leadership, including the Head of School, School Supervisor, Owner, and Teacher which is seen from the presence of intensive training program and one-to-one support with expert trainers provided by the Ministry of Education and Culture. Keywords: Knowledge, Pedagogy, Technology